DEVELOPMENT OF AN INDEPENDENT LIBRARY USING HTML5 TO IMPROVE STUDENTS' DIGITAL LITERACY AT VOCATIONAL SCHOOL - Ovielia Putri Rahman (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The use of information technology in the world of education can produce high quality human resources by improving the quality of education. The aim of this research is to determine the development of an independent library using Html5 to increase the digital literacy of students at Vocational School This research uses literature study, which means collecting and analyzing literature. The results of the research are that technology will continue to advance and develop rapidly. Increasingly advanced technology is a necessity. The emergence of HTML5 is an effort to make technology continue to develop. The emergence of new HTML5 features used in web technology deserves to be considered a technological innovation. HTML5 responds to the development of HTML version 4. HTML5 will continue to be improved and developed by developers and web technology experts so that it can be used in all browsers.